Evaluation of selection based on specific gravity and egg weight for improvement of shell thickness in layer chicken - KHATKAR, M S; S SANDHU, J; BRAH, G S; CHAUDHARY, M L (The Indian Journal of Animal Sciences, 2013)
Data collected on 4 568 pullets of 2 strains of White Leghorn were used for prediction of shell thickness from egg weight, specific gravity and shape index. The R2 values for prediction of shell thickness from specific gravity ranged from 65.69 to 78.01 %. Inclusion of egg weight improved the prediction significant (R2 = 69.9 to 80.0%). Shape index did not improve the efficiency of prediction. Analysis of relative efficiencies of selettion based on specific gravity and an index of specific gravity and egg weight for genetic improvement of shell thickness was made based on genetic parameter estimates. Selection on specific gravity was 7.3% less efficient than direct selection for shell thickness. Selection based on index of specific gravity and egg weight was only 1.6% less efficient than direct selection for shell thickness.